Petrous apicitis and otogenic internal jugular vein thrombosis post cortical mastoidectomy: lessons to learn - Othman, Iylia Ajmal; Abdullah Alwi, Aishah Harizah; Jaafar, Mohd Najib; Abdullah, Asma; Nik Mohd, Nik Khairani (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Petrous apicitis (PA) is a rare and potentially life-threatening condition following otitis media and mastoiditis. Given its rarity and presumed low incidence in the post-antibiotic era, it is often underdiagnosed. Although otogenic lateral sinus thrombosis is widely discussed, not many papers have reported otogenic right internal jugular vein (IJV) thrombosis, specifically in the jugular bulb. Case Report: A 50-year-old female presented with severe right otalgia, retro-orbital pain, and abducens nerve palsy, 2 weeks after emergency cortical mastoidectomy was done in another centre for acute on chronic otitis media with mastoiditis and PA. She was discharged 4 days after the surgery with 1 week of oral antibiotic. Results: Computed Tomography (CT) Venogram showed erosion of the medial wall of the right jugular fossa and the right occipital condyle. The right internal jugular vein (IJV) appeared distended with focal thrombosis at the proximal part of the right IJV within the jugular bulb. Diagnosis of PA complicated with IJV thrombosis was made and medical therapy was initiated. Her treatment regime includes intravenous Ceftriaxone 2 grams twice daily for 2 weeks, followed by oral Cefuroxime 500 milligrams twice daily for 4 weeks. Warfarin 3 milligrams once daily was concurrently prescribed for 12 weeks. Her symptoms improved remarkably after completion of treatment except for persistent diplopia. Conclusion: Advances in radiological assessments coupled with improved antibiotic regime permit more conservative approach in the management of PA. Based on our experience and literature review, we proposed minimum 6 weeks of antibiotic treatment for the management of PA. When concomitant otogenic venous thrombosis is present, selective use of anticoagulant is recommended. If patient clinically worsens or slow to improve with medical therapy, surgical intervention is warranted to reduce disease burden and hasten restoration of middle ear and mastoid aeration via ventilation tube insertion or mastoidectomy.